The empowerment of young girls and women through sport and physical activity participation : a case study in Ethiopia - Alemu, Betelihem (2017)
As a consequence of gender-role socialization, women across the world are still facing unfair perceptions and treatments. Being empowered at the individual level would serve as a platform from which women could combat the existing inequality treatment and perception to gain full control over their lives. Sport and physical activities could serve as a platform for women to gain control. The aim of this research is to explore the potential that sport and physical activity (PA) have in the empowerment of young girls and women in Ethiopia. Additional questions were used in order to further explore any disempowerment experiences as a result of sport and physical activity participation, barriers that limits participations and recommendation from participants to further strengthen the participation of young girls and women in sport and physical activities in Ethiopia. The study uses Zimmerman’s empowerment theoretical framework to evaluate potential empowerment through the participation in sport and PA at an individual level. The study adopted as qualitative case study research design. In personal semi-structured interviews was conducted with 12 young girls and women between the age of 16 to 20 who are currently participating in different sport and PA. Thematization was used to organize interview data and select themes from the interviews which played significant role in the formulating an in-depth understanding how sport and PA has enhance the empowerment of young girls and women in Ethiopia. Result suggested that sport and PA actually has enhanced the empowerment of young girls and women a) critical thinking b) perception of self-competence c) social support and network d) healthy and active life. However, the research also found that there were disempowerment outcomes including violence and financial burden that young girls and women face in their sport and PA participation. Though young girl and women participation in sport and PA in Ethiopia is enabling them to gain control over their life, they are still way behind their male counters in the quality, access and inclusiveness in the area of sport. There are still endless work to do to create safe, affordable and inclusive sport and PA culture within the Ethiopian society. This research recommend providing financial assistance, coach trainings and community outreach as a start.